Access point Selection in 802.11 Wireless Networks Guaranteeing Minimum QoS (2014)
In this paper we present the research results that conducted to address the problem of associating a user to a wireless access point (AP) in a multicell 802.11 network in which service a large number of users, each user selfishly is connected to the acces